Addressing the asthma crisis in Africa: challenges, strategies, and recommendations for improved management - Ayodeji Amos Faniyi; Olalekan John Okesanya; Ruth Nimota Nukpezah; Deborah Oluwaferanmi Ibiwoye; Gilbert Eshun; Olaniyi Abideen Adigun; Inibehe Ime Okon; Bonaventure Michael Ukoaka; Olaleke Noah Olabode; Don Lucero-Prisno Eliseo (SpringerOpen, 2024)
Abstract Asthma poses a significant health burden in Africa despite being often underdiagnosed and undertreated. With rising incidence rates and large variations in healthcare infrastructure, its management remains threatened by limited access to medical resources and qualified specialists. The prevalence of asthma in Africa is highlighted, with broad estimates and insufficient information on the disease's burden and determinants. In addition to diagnostic challenges, under treatment, medication unavailability, sociocultural misunderstandings, and poor healthcare infrastructure remain the hallmarks of asthma management in Africa. This review synthesized evidence on the prevalence of asthma in Africa, explored the challenges in managing asthma across the continent, and proposed potential strategies to improve treatment outcomes. Literature was obtained via electronic databases, including PubMed, Web of Science, and Scopus, with additional searches conducted via Google Scholar to identify all available studies. Studies have reported a staggeringly high prevalence of asthma, exceeding 12% on average. Notably, a significant number of these cases are suboptimally controlled, with limited access to healthcare and deficiencies in healthcare delivery systems identified as major contributing factors. Numerous strategies have been proposed to circumvent the limitations faced in effective asthma management. Measures such as the development of national and regional evidence-based asthma guidelines, the provision of affordable medicines and diagnostic equipment, and the improvement of community-based asthma education programs can expedite the goals of asthma control programs. Furthermore, reorienting health systems to incorporate asthma care into primary care and investing in human resource capacity are critical steps. Adopting evidence-based treatment guidelines, such as those established by the Global Initiative for Asthma (GINA), can drastically reduce asthma morbidity and mortality. Through concerted collaboration and synergistic integration of these strategies, the potential for effective asthma management across the continent holds, transcending existing disparities and ushering in an era of improved healthcare services for individuals grappling with this chronic respiratory ailment in Africa.